249 lines
11 KiB
TeX
249 lines
11 KiB
TeX
% !TeX root = ../../script.tex
|
|
\documentclass[../../script.tex]{subfiles}
|
|
|
|
\begin{document}
|
|
\section{Fourier Transform on $L^1(\realn^d)$}
|
|
|
|
\begin{defi}
|
|
For $f \in L^1(\realn^d)$ the function
|
|
\begin{align*}
|
|
\hat{f}: \realn^d &\longrightarrow \cmpln \\
|
|
k &\longmapsto \rec{(2\pi)^{\frac{d}{2}}} \int_{\realn^d} e^{-ik \cdot x} f(x) \dd{x}
|
|
\end{align*}
|
|
is said to be the Fourier transform of $f$. Sometimes it is written as $(\mathcal{F}f)(k)$.
|
|
\end{defi}
|
|
|
|
\begin{rem}
|
|
\begin{enumerate}[(i)]
|
|
\item There are several alternative conventions regarding sign and phase of the transform.
|
|
\[
|
|
\hat{f}(k) = \int_{\realn^d} e^{-2\pi ik \cdot x} f(x) \dd{x}
|
|
\]
|
|
is also a valid definition in other scientific fields, however we will stick to the former definition throughout this script.
|
|
|
|
\item $k \cdot x = \innerproduct{k}{x} = \sum_{j=1}^d k_j x_j$
|
|
\item Because $\abs{e^{ik \cdot x}} = 1$, the integral exists for any $f \in L^1(\realn^d)$.
|
|
\end{enumerate}
|
|
\end{rem}
|
|
|
|
\begin{eg}\label{eg:1}
|
|
Consider the function
|
|
\[
|
|
f(x) = \rec{\sqrt{2\pi\sigma^2}} e^{-\frac{(x - \alpha)^2}{2\sigma^2}} \quad ,\alpha \in \cmpln, ~\sigma > 0
|
|
\]
|
|
The Fourier transform is
|
|
\begin{align*}
|
|
\hat{f}(k) = &\rec{2\pi\sigma} \int_{\realn} e^{-ikx} e^{-\frac{(x - \alpha)^2}{2\sigma^2}} \dd{x} \\
|
|
= &\rec{2\pi\sigma} e^{-ik\alpha} e^{-\frac{\sigma^2}{2} k^2} \int_{\realn} e^{-\frac{(x - \alpha + ik\sigma^2)^2}{2\sigma^2}} \dd{x} \\
|
|
= &\rec{2\pi\sigma} e^{-ik\alpha} e^{-\frac{\sigma^2 k^2}{2}} \int_{-\infty}^{\infty} e^{-\frac{x^2}{2\sigma^2}} \dd{x} \\
|
|
= &\rec{\sqrt{2\pi}} e^{-ik\alpha} e^{-\frac{\sigma^2 k^2}{2}}
|
|
\end{align*}
|
|
\end{eg}
|
|
|
|
\begin{eg}
|
|
The previous example can be generalized for higher dimensions:
|
|
\[
|
|
f(x) = \rec{(2\pi\sigma^2)^{\frac{d}{2}}} e^{-\frac{\abs{x}^2}{2\sigma^2}}, \quad x \in \realn^d
|
|
\]
|
|
With the Fourier transform
|
|
\[
|
|
\hat{f}(k) = \rec{(2\pi)^{\frac{d}{2}}} e^{-\frac{\sigma^2 \abs{k}^2}{2}}, \quad k \in \realn^d
|
|
\]
|
|
\end{eg}
|
|
|
|
\begin{eg}
|
|
Consider the indicator function
|
|
\[
|
|
\chi(x) = \begin{cases}
|
|
1, & \abs{x} \le a \\
|
|
0, & \abs{x} > a
|
|
\end{cases}, \quad x \in \realn
|
|
\]
|
|
It has the Fourier transform
|
|
\[
|
|
\hat{f}(k) = \rec{\sqrt{2\pi}} \int_{\realn} e^{-ikx} \chi(x) \dd{x} = \rec{\sqrt{2\pi}} \left[ \frac{e^{-ikx}}{-ik} \right]_{-a}^a = \sqrt{\frac{2}{\pi}} \frac{\sin(ka)}{k}
|
|
\]
|
|
\end{eg}
|
|
|
|
\begin{defi}
|
|
For $f \in L^1(\realn^d)$ the function
|
|
\[
|
|
\check{f}(x) := \rec{(2\pi)^{\frac{d}{2}}} \int_{\realn^d} f(k) e^{ikx} \dd{k}
|
|
\]
|
|
defines the inverse Fourier transform of $f$.
|
|
\end{defi}
|
|
|
|
\begin{eg}
|
|
Let's revisit \Cref{eg:1}, where we found that
|
|
\[
|
|
\hat{f}(k) = \rec{\sqrt{2\pi}} e^{-i\alpha k} e^{-\frac{\sigma^2 k^2}{2}}
|
|
\]
|
|
The inverse Fourier transform of that function is
|
|
\[
|
|
\check{\hat{f}}(k) = \rec{\sqrt{2\pi\sigma^2}} e^{-\rec{2\sigma^2} (x - \alpha)^2} = f(x)
|
|
\]
|
|
\end{eg}
|
|
|
|
\begin{thm}[Fourier inversion theorem]
|
|
Let $f, \hat{f} \in L^1(\realn^d)$. Then $\check{\hat{f}} = f$.
|
|
\end{thm}
|
|
|
|
\begin{proof}
|
|
To prove this theorem we will use \Cref{thm:10.42} and the following lemma:
|
|
\bigbreak
|
|
\begin{itshape}
|
|
If $f_n \conv{n \rightarrow \infty} f$, then there exists a subsequence $((f_n)_k)_{k \in \natn}$ with
|
|
\[
|
|
\lim_{k \rightarrow \infty} f_{n_k} (x) = f(x), \quad \forall x \in \realn^d
|
|
\]
|
|
\end{itshape}
|
|
\bigbreak
|
|
Heuristically this theorem can be proven by considering
|
|
\begin{equation}
|
|
\begin{split}
|
|
\check{\hat{f}}(x) = \rec{(2\pi)^{\frac{d}{2}}} \int_{\realn^d} \hat{f}(k) e^{ikx} \dd{k}
|
|
&= \rec{(2\pi)^{\frac{d}{2}}} \int_{\realn^d} \left( \int_{\realn^d} f(y) e^{-iky} \dd{y} \right) e^{ikx} \dd{k} \\
|
|
&= \rec{(2\pi)^{\frac{d}{2}}} \int_{\realn^d} \int_{\realn^d} f(y) e^{-ik(y - x)} \dd{k} \dd{y}
|
|
\end{split}
|
|
\end{equation}
|
|
However, to show this rigorously we should first consider the inversion formula for $f * \delta_l$, with
|
|
\begin{equation}
|
|
\delta_l (x) = \left( \frac{l^2}{2\pi} \right)^{\frac{d}{2}} e^{-\frac{l^2 \abs{x}^2}{2}}, \quad l \in \natn
|
|
\end{equation}
|
|
The Fourier transform is
|
|
\begin{equation}
|
|
\hat{\delta_l} (k) = \left(\rec{2\pi}\right)^{\frac{d}{2}} e^{-\frac{\abs{k}^2}{2l^2}}
|
|
\end{equation}
|
|
We've already shown in a previous example that the inversion theorem applies to this function, so we can write
|
|
\begin{equation}
|
|
\begin{split}
|
|
(f * \delta_l)(x) &= \int_{\realn^d} f(y) \delta_l(x - y) \dd{y} = \int_{\realn^d} f(y) \check{\hat{\delta}}_l(x - y) \dd{y} \\
|
|
&= \int_{\realn^d} f(y) \left( \rec{(2\pi)^{\frac{d}{2}}} \int_{\realn^d} e^{ik(x - y)} \hat{\delta}_l (k) \dd{k} \right) \dd{y}\\
|
|
&= \int_{\realn^d} \left(\rec{(2\pi)^{\frac{d}{2}}} \int_{\realn^d} f(y) e^{-iky} \dd{y} \right) e^{ikx} \hat{\delta_l} (k) \dd{k} \\
|
|
&= \int_{\realn^d} e^{ikx} \hat{f}(k) e^{-\frac{\abs{k}}{2l^2}} \frac{\dd{k}}{(2\pi)^{\frac{d}{2}}} =: \check{F}_l(x)
|
|
\end{split}
|
|
\end{equation}
|
|
Next we want to use the fact that $(\delta_l)_{l \in \natn}$ is a class of good kernels. This means that
|
|
\begin{equation}
|
|
\lim_{l \rightarrow \infty} \norm{\delta_l * f - f}_{L^1} = 0
|
|
\end{equation}
|
|
or in other words
|
|
\begin{equation}
|
|
\delta_l * f \conv{l \rightarrow \infty} f
|
|
\end{equation}
|
|
Now using the lemma above we can conclude that there exists a subsequence $(\delta_{l_j} * f)_{j \in \natn}$ that converges to $f(x)$ for almost every $x$.
|
|
We can apply the dominated convergence theorem to find that
|
|
\begin{equation}
|
|
\lim_{l \rightarrow \infty} \check{F}_l(x) = \int_{\realn^d} e^{ikx} \hat{f}(k) \lim_{l \rightarrow \infty} e^{-\frac{\abs{k}^2}{2l^2}} \frac{\dd{k}}{(2\pi)^{\frac{d}{2}}} = \check{\hat{f}}(x)
|
|
\end{equation}
|
|
Finally, this lets us conclude
|
|
\begin{equation}
|
|
f(x) = \lim_{j \rightarrow \infty} \delta_{l_j} * f(x) = \lim_{j \rightarrow \infty} \check{F}_{l_j} (x) = \check{\hat{f}}, \quad \text{for a.e. } x \in \realn^d
|
|
\end{equation}
|
|
\end{proof}
|
|
|
|
\begin{thm}[Algebraisation of the derivative]
|
|
Let $f \in C^n(\realn^d)$ and $\partial^{\alpha} f \in L^1(\realn^d)$ for all $\alpha \in \natn_0^d$ with $\abs{\alpha} < m$. Then
|
|
\[
|
|
\widehat{\partial^a f}(k) = (ik)^{\alpha}\hat{f}
|
|
\]
|
|
If $\alpha = (\alpha_1, \cdots, \alpha_d)$ and $\abs{\alpha} = \sum_{j=1}^d \alpha_j \le m$, then the interpretation of that is
|
|
\[
|
|
\mathcal{F}\left(\frac{\partial^{\abs{\alpha}}}{\partial x_1^{\alpha_1} \cdots \partial x_d^{\alpha_d}} f\right)(k) = i^{\abs{\alpha}} \left(k_1^{\alpha_1} \cdots k_d^{\alpha_d}\right) \hat{f}(k)
|
|
\]
|
|
\end{thm}
|
|
\begin{proof}
|
|
We will only prove the one-dimensional statement. If $m = 1$ we receive via partial integration
|
|
\begin{equation}
|
|
\widehat{f'}(k) = \rec{\sqrt{2\pi}} \int_{\realn} f'(x) e^{-ikx} \dd{x} = \rec{\sqrt{2\pi}} \left[ \left(f(x) e^{-ikx}\right)_{-\infty}^{\infty} - \int_{-\infty}^{\infty} f(x) \dv{x} \left(e^{-ikx}\right) \dd{x} \right]
|
|
\end{equation}
|
|
Since we assumed $f' \in L^1$, the limit $\lim_{x \rightarrow \pm\infty} f(x)$ exists. We can write
|
|
\begin{align}
|
|
f(x) &= f(0) + \int_0^x f'(t) \dd{t} \\
|
|
\implies \lim_{x \rightarrow \pm\infty} f(x) &= f(0) + \lim_{x \rightarrow \pm\infty} \int_0^x f'(t) \dd{t}
|
|
\end{align}
|
|
Furthermore this limit has to be equal to $0$, so
|
|
\begin{align}
|
|
\lim_{\abs{x} \rightarrow \infty} f(x) &= 0 \\
|
|
\implies \left[f(x) e^{-ikx}\right]_{-\infty}^{\infty} &= \lim_{x \rightarrow \infty} e^{-ikx} f(x) - \lim_{x \rightarrow \infty} f(x)e^{ikx} = 0
|
|
\end{align}
|
|
This leads us to
|
|
\begin{equation}
|
|
\widehat{f'}(k) = ik \rec{\sqrt{2\pi}} \int_{\realn} f(x) e^{-ikx} \dd{x} = ik\hat{f}(k)
|
|
\end{equation}
|
|
The proof for $m > 1$ can be found via induction.
|
|
\end{proof}
|
|
|
|
\begin{thm}
|
|
Let $f \in L^1(\realn^d)$ and $m \in \natn_0$. If
|
|
\[
|
|
x \longmapsto x^{\alpha} f(x) \in L^1(\realn^d), \quad \forall \alpha \in \natn_0^d, ~\abs{\alpha} \le m
|
|
\]
|
|
then $\hat{f} \in C^m(\realn^d)$ and
|
|
\[
|
|
\partial^{\alpha} \hat{f}(k) = \mathcal{F}\left[(-ix)^{\alpha} f(x)\right](k)
|
|
\]
|
|
\end{thm}
|
|
\begin{proof}
|
|
Again we will only consider the one-dimensional case. Assume $m = 1$ (the proof for $m > 1$ follows from induction).
|
|
We can write out the difference quotient for $\hat{f}$ at $k \in \realn$
|
|
\begin{equation}
|
|
\frac{\hat{f}(k + h) - \hat{f}(k)}{h} = \rec{h} \int_{\realn} f(x) \left(e^{-i(k + h)x} - e^{-ikx}\right) \frac{\dd{x}}{\sqrt{2\pi}}, \quad h \in \realn \setminus \set{0}
|
|
\end{equation}
|
|
However, because
|
|
\begin{equation}
|
|
\abs{\frac{e^{-ixh} - 1}{h}} \le \abs{x}, \quad \forall x \in \realn, ~h \ne 0
|
|
\end{equation}
|
|
and because we assumed that $xf \in L^1$, we can use the dominated convergence theorem to conclude
|
|
\begin{equation}
|
|
\begin{split}
|
|
\lim_{h \rightarrow 0} \frac{\hat{f}(k + h) - \hat{f}(k)}{h} &= \rec{\sqrt{2\pi}} \int_{\realn} f(x) e^{-ikx} \underbrace{\lim_{h \rightarrow 0} \left(\frac{e^{-ixk} - 1}{h}\right)}_{\dv{x} \left(e^{-ikx} \right) \big|_{x = 0}} \dd{x} \\
|
|
&= \rec{\sqrt{2\pi}} \int_{\realn} (-ixf(x)) e^{-ikx} \dd{x} = \widehat{-ixf}(k)
|
|
\end{split}
|
|
\end{equation}
|
|
\end{proof}
|
|
|
|
\begin{thm}
|
|
Let $f, g \in L^1(\realn^d)$. Then
|
|
\[
|
|
\widehat{f*g}(k) = (2\pi)^{\frac{d}{2}} \hat{f}(k) \hat{g}(k)
|
|
\]
|
|
\end{thm}
|
|
\begin{proof}
|
|
\noproof
|
|
\end{proof}
|
|
|
|
\begin{eg}[Solving inhomogeneous, linear ODEs]
|
|
We want to find the general solution of
|
|
\[
|
|
\ddot{x} - x = f, \quad f, \hat{f} \in L^1(\realn)
|
|
\]
|
|
The solution space of this equation is
|
|
\[
|
|
\mathcal{L} = \mathcal{L}_{\text{hom}} + x_s
|
|
\]
|
|
The space of homogeneous solutions $\mathcal{L}_{\text{hom}}$ is equal to $\spn\set{e^x, e^{-x}}$, and $x_s$ is \textit{one} solution of the inhomogeneous equation.
|
|
Let $\phi$ denote the Fourier transform of $x_s$, so
|
|
\[
|
|
\phi(k) = \rec{\sqrt{2\pi}} \int_{\realn} x_s(t) e^{-ikt} \dd{t}
|
|
\]
|
|
Then $\phi$ satisfies the equation
|
|
\[
|
|
-k^2 \phi(k) - \phi(k) = \hat{f}(k)
|
|
\]
|
|
Or rearraranged to solve for $\phi$
|
|
\[
|
|
\phi(k) = -\rec{1+k^2} \hat{f}(k), \quad k \in \realn
|
|
\]
|
|
We can then rewrite $\phi(k)$ as
|
|
\begin{align*}
|
|
\phi(k) = -\hat{g}(k) \hat{f}(k) && \text{with } \hat{g} = \rec{1 + k^2} \in L^1(\realn)
|
|
\end{align*}
|
|
and then use the previous theorems to conclude
|
|
\[
|
|
x_s(t) = \check{\phi}(t) = (2\pi)^{\frac{1}{2}} \inv{\mathcal{F}} \underbrace{\left[ \hat{f}\hat{g} (2\pi)^{\frac{1}{2}}\right]}_{\widehat{f*g}}(t) = -\rec{\sqrt{2\pi}}(f*g)(t)
|
|
\]
|
|
\end{eg}
|
|
|
|
\end{document}
|